The interaction between anti-Ro/SSA and anti-La/SSB autoantibodies and anti-infectious antibodies in a wide spectrum of auto-immune diseases: Another angle of the autoimmune mosaic (2017)
Objective The presence of anti-Ro/SSA and anti-La/SSB antibodies has been linked with autoimmunity in general and with several autoimmune diseases (AID) in particular. In the current study we evaluated these antibodies in a wide spectrum of AID as well as the links between them and anti-infectious antibodies Methods We examined 2082 sera from patients with 16 different AID compared to 524 sera from geographically-matched healthy controls, for the presence and titres of anti-Ro/SSA and anti-La/SSB. All samples were also tested for a variety of anti-infectious agents' antibodies using the BioPlex 2200-immunoassay (Bio-Rad, USA). Results Anti-Ro/SSA was more prevalent, with significantly higher titre in 5 autoimmune diseases namely Sjögren's syndrome (SS), systemic lupus erythematosus (SLE), antiphospholipid syndrome (APS) both primary and APS linked to SLE, systemic sclerosis (SSc) and primary biliary cirrhosis (PBC). Anti-La/SSB was more prevalent with higher titers in SS, SLE, APS linked to SLE and PBC. Prevalence, but not titers, of both antibodies were higher also in polymyositis (PM). Additionally, we found a correlation between anti-Ro/SSA antibodies and antibodies of the IgM and IgG subtypes directed at cytomegalovirus as well as IgG-antibodies directed at Epstein-Barr virus (EBV) and toxoplasma (p less than 0.001). Anti-La/SSB antibodies correlated with the presence of IgG antibodies against EBV early antigen (p less than 0.001). Conclusion In a large cohort of patients with autoimmune diseases we found an association between anti-Ro/SSA and anti-La/SSB antibodies and 6 autoimmune diseases, amongst which primary APS and PM. Additionally, we observed linkages between these autoantibodies and anti-infectious antibodies directed at Epstein-Barr virus, toxoplasma and cytomegalovirus. Our findings support the concept of interplay between infectious agents and autoimmunity, such as the plausibility of an infectious agent that trigger the immune system to produce specific antibodies which will later result in a unique group of AID. © Clinical and Experimental Rheumatology 2017.